Contesting the Inclusive Islam Discourse in the Public Sphere: Insights from Southeast Asia - Muhtador, Moh; Ulya, Ulya (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2024)
The narratives of peace, humanity, and religious freedom have become central to public discourse, particularly in promoting inclusive Islamic theology within Muslim communities across ASEAN countries, e.g. Indonesia, Malaysia, Singapore, Thailand, and the Philippines. This discourse unfolds in various public spaces: government institutions, religious organizations, educational settings, and places of worship. It reflects a dynamic religious contestation, driven by organic intellectuals who engage through institutional channels and humanistic awareness. This article seeks to explore the religious discourse surrounding the productive contestation of inclusive Islamic theology and to analyze how this discourse is disseminated among Muslim scholars in Southeast Asia. A qualitative research method was employed, involving observations and interviews with influential Muslim scholars from academic, governmental, and religious organizations. The focus was on understanding how individuals are shaped by the policies and ideas they advocate. Interviews provided insights from academics and religious activists (referred to as Muslim scholars) on the issue of inclusive Islamic theology. The analysis draws on contestation theory to examine the arena of religious narratives in the public sphere. Findings indicate that the discourse surrounding inclusive Islamic theology in Southeast Asia varies by country, with each nation adapting it to its unique cultural and social landscape. In Indonesia, for example, the discourse is often more inclusive and culturally grounded, while in other countries, it may take a more structural approach. Despite these variations, Southeast Asian Muslim scholars broadly agree on the importance of promoting inclusive Islamic theology drawing upon religious teachings, state policies, and societal characteristics as key considerations.